Donor ABCB1 variant associates with increased risk for kidney allograft failure - Moore, Jason; Döhler, Bernd; Opelz, Gerhard (Journal of the American Society of Nephrology, 2012)
The impact of variation within genes responsible for the disposition and metabolism of calcineurin inhibitors (CNIs) on clinical outcomes in kidney transplantation is not well understood. Furthermore, the potential influence of donor, rather than recipient, genotypes on clinical endpoints is unknown. Here, we investigated the associations between donor and recipient gene variants with outcome among 4471 white, CNI-treated kidney transplant recipients. We tested for 52 single-nucleotide polymorphisms (SNPs) across five genes: CYP3A4, CYP3A5, ABCB1 (MDR1; encoding P-glycoprotein), NR1I2 (encoding the pregnane X receptor), and PPIA (encoding cyclophilin). In a discovery cohort of 811 patients from Birmingham, United Kingdom, kidney donor CC genotype at C3435T (rs1045642) within ABCB1, a variant known to alter protein expression, was associated with an increased risk for long-term graft failure compared with non-CC genotype (hazard ratio [HR], 1.69; 95% confidence interval [CI], 1.20-2.40; P=0.003). No other donor or recipient SNPs were associated with graft survival or mortality. We validated this association in 675 donors from Belfast, United Kingdom (HR, 1.68; 95% CI, 1.21-2.32; P=0.002), and in 2985 donors from the Collaborative Transplant Study (HR, 1.84; 95% CI, 1.08-3.13; P=0.006). In conclusion, these data suggest that an ABCB1 variant known to alter protein expression represents an attractive candidate for future study and risk stratification in kidney transplantation.
Gesehen am 03.05.2018